Application of Formative Assessment to Measure Students' Self-Regulation in Physics Lessons - Nanda Ima Nafila; Abu Zainuddin (Universitas Muhammadiyah Makassar, 2022)
In the world of education, formative assessment is critical because it is to know the growth of students when doing a lesson and get an idea regarding the way the teacher develops learning methods that occur. The purpose of the study was to determine the application of formative assessment to measure students' self-regulation. This study's data collection methods used questionnaires and test questions with data analysis techniques using qualitative descriptive. Respondents in this study amounted to 35 students of class XI IPA 4 SMA Negeri 14 Surabaya. The results showed that self-regulation or the ability to regulate oneself in students could be known and measured using the application of formative assessment. The self-assessment results on students are more striking when measured using a questionnaire. They can use seven categories of self-regulation to assess and observe their expertise, skills, competencies, and performance presented in the form of a questionnaire. Self-regulation ability that can measure is undoubtedly beneficial for the future orientation of students in motivating and controlling their learning process. In addition, with the application of formative assessment, teachers get feedback on the learning process that is being developed to monitor the progress and growth of students during the learning process.